0029 Evaluating a training program to increase infant safe sleep counselling in massachusetts. (26th April 2015) - Treadway, Nicole; Howland, Jonathan; Taylor, Alyssa; McCarthy-Licorish, Lisa; Egan, Justine; Lu, Emily; Diop, Hafsatou; Colchamiro, Racheld; Mendoza, Terri Grodner; Hackman, Holly; Kautz-Mills, Julie; Nelson, Kerrie
Abstract : Statement of purpose: An average of 41 infants died each year during 2004–2010 in Massachusetts due to sudden unexplained infant death (SUID). Safe sleep practices can reduce SUID risk. Approximately 40% of new mothers in Massachusetts are enrolled in the Women, Infants, and Children (WIC) program. WIC provides a platform for deploying information on safe sleep practices. The purpose of our study is to evaluate a train-the trainer program among WIC counsellors to promote safe-sleep practices among post-partum WIC enrolled mothers. Methods/Approach: A statewide train-the trainer program was conducted among WIC area office supervisors, who subsequently trained their staff on the revised (2011) American Academy of Paediatrics safe sleep recommendations. Pre-posttest assessments measured program impacts (knowledge, attitudes, behaviours) 6-months post intervention. Herein we report on WIC counsellors' safe sleep client counselling behaviours. Counsellors were asked how many of their clients they had counselled in the last month about: (1) safe sleep positioning; (2) safe crib contents; and (3) risks of co-sleeping. Response categories were: None; Some; Half; Most; and All. Results: Six month posttests were completed by 68% of WIC staff. Of staff whose jobs involved client counselling, 278 received training. Pre-posttest changes in proportions of trained counsellors who reported counselling" most or all" of their clients were: 11% (pretest) to 38% (posttest) for safe sleep positioning; 8% (pretest) to 28% (posttest) for safe crib contents; and, 9.7% to 32% for risks of co-sleeping. Conclusions: WIC counsellors were more apt to promote safe sleep practices after receiving the intervention. Around 40% of new mothers in Massachusetts are enrolled in WIC. Thus, training WIC counsellors could be an efficient and effective method for promoting safe sleep practices. Significance and contribution to the field: Safe sleep practices can reduce risk of SUID among WIC participants. The WIC program provides a unique venue to share information on best infant sleep practices. This program could serve as a national model for promoting safe-sleep.